Persistensi Pendampingan Keluarga Terhadap Anggota Keluarga yang Sakit Sebagai Pencegahan Penularan Mycobacterium Tuberkulosis di Serdang Bedagai - Nixson Manurung; Rostinah Manurung; Christina Magdalena T; Ratna Dewi; Sarmaida Siregar (Pusat Riset dan Inovasi Nasional, 2023)
The increasing burden of TB is caused by poverty, the failure of TB activities which has been caused by inadequate political commitment and funding, the unavailability of services in the community causing reduced problem innovation and inappropriate diagnosis, reduced supply of medicines and reduced reporting of tuberculosis sufferers, lack of surveillance, minimal discourse on recording and reporting cases, treatment management and unreported movement of people. The method used was descriptive observational with 20 participants who were families of tuberculosis sufferers at the Serdang Bedagai health center. The PkM team provided the material in question: 1) Understanding family persistence, 2) The importance of family in accompanying TB sufferers, 3) How to prevent transmission, and 4) Patient compliance in taking medication. Results after carrying out the activity 1) Understanding family persistence, the majority of them were good, 18 people, 2) The importance of families accompanying TB sufferers, the majority of them were good, 19 people, 3) Ways to prevent transmission, the majority were good, 19 people, 4) Compliance with patients in taking medication, the majority were good, 19 person. The persistence of family assistance to sick family members as a means of preventing the transmission of mycobacterium tuberculosis shows improvement and skills because people have a great desire to treat and prevent the occurrence of tuberculosis in family members at home.